The Legal Status of Ai-Based Works of Art: A Study on AI as the Subject of Copyright in Indonesia - Maulana Deden Karoma; Nurul Shofwan Adha; Awal Rusdi Maulana; Ikhwan Aulia Fatahillah (Journal of Human Interaction and Social Studies, 2026)
This study examines the regulatory challenges and doctrinal tensions arising from the proliferation of artificial intelligence in the Indonesian creative economy, with a specific focus on the legal status of algorithmic art. Utilizing a non-empirical normative legal research design incorporating the statute, conceptual, and comparative approaches, the investigation dissects the structural limitations of Law Number 28 of 2014 on Copyright. The analytical framework reveals that Indonesian jurisprudence strictly binds legal subjectivity to human consciousness and corporate entities, creating an insurmountable barrier for autonomous software to achieve independent authorship or claim moral rights. Furthermore, comparative insights from the United States and the European Union demonstrate that unregulated data scraping and algorithmic duplication pose severe economic threats to human creators and communal digital cultural heritage. Ultimately, this study proposes a comprehensive future regulatory model through modified ownership doctrines and specialized statutory frameworks to secure market certainty without disrupting the anthropocentric foundations of national intellectual property law.